Representações sobre violência na escola: um olhar antropológico a respeito da violência em duas escolas do município de Tabatinga-AM - Broetto, João Victor Santos (Brasil, 2024)
Violence in schools is a problem that encompasses the most different levels of the school institution, in Tabatinga the topic of school violence is crossed by border violence, and the extra walls condition directly affects the way in which students construct perceptions about the subject. Through this research we sought to develop an analysis regarding the violence that exists in the school environment. Using this data, we delve deeper into some aspects that we consider most significant to reflect on violence at school and develop my course completion monograph. We propose this study with the aim of better understanding the perceptions of these young people about violence in the school environment, verifying the questions that develop from these perceptions on the topic. The work was developed using the participant observation technique over a period of one year, between 2022 and 2023, with students from two high schools in the city of Tabatinga-AM, Escola Estadual Conceição Xavier de Alencar (GM3) and Centro Educacional de tempo integral Joao Carlos Pereira dos Santos (CETI). Through this work we seek to understand how violence populates the social imagination of students and sometimes what leads them to reproduce, even if unconsciously, the violence to which they are subjected, be it disciplinary and symbolic violence from educational institutions themselves, or extra violence walls, which populate the imagination of these young people, and are reproduced in the school environment through symbols that are adopted and reproduced by them.